Impacts of Cyber Security and Supply Chain Risk on Digital Operations - Del Giorgio Solfa, Federico (2022)
The research explored empirical evidence to assess the impact of cyber security and supply chain risk on digital operations in the UAE pharmaceutical industry. Based on responses from 243 personnel working at 14 pharmaceutical manufacturing companies in Dubai, data were examined for normality, instrument validity and regression analysis. Cyber security and SC risk on digital operations were explored by applying convenient sampling and descriptive and analytical research design. The findings validated the significant positive association between cyber security and supply chain risk with digital operations. The research model was developed with three variables evaluated only on the pharmaceutical industry in Dubai. Future research should focus on multiple manufacturing industries by covering a larger geographic area. When suppliers are highly concentrated, customer-focused organizations with uncertain levels of digital transformation could improve their ability to manage supply chain risk by diversifying their clients. Pharmaceutical firms may require a greater focus on technology-based manufacturing firms to build and maintain customer trust. To illustrate how the pharmaceutical industry has explored the relationship between cyber security, supply chain risk and digital operations, the research highlights the significant and convoluted consequences of the relationship model that have not been previously considered.